How to successfully advocate for a second business librarian - Price, Elizabeth; Schubert, Carolyn (Ticker, 2024)
In a New York Times article about higher education budget cuts affecting humanities programs, Anemona Hartocollis reported that the most popular majors in 1970 were education, social sciences and history degrees; whereas “Today, the most popular degree is business, at 19 percent of all bachelor’s degrees, while social sciences trail far behind at just 8 percent of degrees” (Hartocollis, 2023). In her review of institutional data, Carolyn observed that business enrollment had grown about 40% over the previous six years while social sciences enrollment was steady or slightly declining (James Madison University, Office of Planning, Analytics and Institutional Research. n.d.). Using that list, she reviewed websites of the institutional research offices at each university to get business school enrollment and faculty totals in the summer of 2017. Comparing data across JMU’s 11 liaison librarians, including the business librarian. x-The reason different dates were used for the counts for faculty and students is a result of the different data collection and reporting cycles from JMU’s Office of Planning, Analytics and Institutional Research and what information was available when the initial review by liaison was developed. y-Average per librarian excludes the business librarian’s data. z-During the 2020-21 academic year, all librarians were pitching in to staff the Ask the Library chat service, and each chat was counted as a consultation.